Thoracic Anatomy Tutorial Using an Imaging Platform - Michelle Lazarus; Allison Stanley; Lindsay Smith; Pamela Brian (Association of American Medical Colleges, 2014)
Abstract Introduction This tutorial was developed in response to the current trend in undergraduate medical education to focus on self-directed learning. To this end, the authors developed this tutorial to introduce clinical anatomy and radiology basics to beginner medical students. This thoracic tutorial was developed through a collaborative effort between medical students, a clinical radiologist, and an anatomist, and results in a tutorial that highlights student perceptions of valuable anatomical concepts and those deemed applicable by clinical and basic science faculty. Methods This resource contains a self-guided interactive computer tutorial. The tutorial's PowerPoint presentation contains slides featuring labeled thoracic structures using radiologic image such as plain films, CT, and MR images. These slides are enhanced with anatomic relationships, quiz questions, radiology reading basics, and clinical correlates. The interactive PowerPoint format allows students to accomplish individual learning goals at an appropriate pace and transition basic science knowledge into clinical years. This tutorial is intended to be utilized as a self-guided review of thoracic anatomy and allows the user to revisit difficult or interesting topics. Results We evaluated the impact of this thorax imaging tutorial on medical student anatomy learning using objective repeated measures and student self-efficacy evaluations. The study population consisted of volunteer first-year medical students participating in the anatomy course at The Pennsylvania State College of Medicine during the 2012-13 and 2013-14 academic years. Students were randomly divided into intervention and control groups. The control group (n = 28) received only basic traditional anatomy instruction. The intervention group (n = 25) received this same anatomy instruction plus thorax tutorial access for up to 1 hour. Tutorial access resulted in an overall significant improvement of tested knowledge (+8.2% with thoracic tutorial access, p ≤ 0.05). The most significant improvement was in the structure identification of radiologic images (+28.8% with thoracic tutorial access, p ≤ 0.05). Self-efficacy subjective studies revealed that students felt that: this tutorial was beneficial to their learning of anatomy (96%); they would use this type of tutorial at least weekly during anatomy coursework (80; and, they would revisit this tutorial throughout their medical school education (92%). Discussion This self-guided interactive computer tutorial successfully enhances medical student thoracic anatomy learning using radiologic imaging through interactive self-learning. The authors contend, and results demonstrate, that the inclusion of anatomical and clinical knowledge beyond simple labeling of radiological images adds a novel educational dimension that may prove very useful in teaching at many medical schools.